Relationship Between Cleft Lip and Palate Followed by Osteogenesis Imperfecta Accompanied by Tetralogy of Fallot in Children with a Maternal History of Catatonic Schizophrenia with Valproic Acid Therapy and Diabetes Mellitus - R. Mohamad Javier; Abdillah Budi Ksatria; Andisa Fadhila Rialdi; Syarif Syamsi Ahyandi; Revita Widya Prasanti; Himawan Wicaksono; Budi Prakoso; Maisuri; Bambang Widiwanto; A. Rusli Budi Ansyah (Jurnal Multidisiplin Madani, 2023)
Researchers believe that most cases of cleft lip and cleft palate are caused by genetic and environmental factors. Nevertheless, the exact cause was not found. Nevertheless there are allegations that the condition of the cleft lip and palate has something to do with osteogenesis imperfecta with the heterozygous mutation COL1A2 and the formation of triple helix DNA accompanied by Tetralogy of Fallot in children with a maternal history of catatonic schizophrenia followed by the use of valproic acid and type II diabetes mellitus. Then, it is also found in babies with cleft lip and sky conditions usually accompanied by other congenital anomaly, but not always. This then further gives rise to speculation that there are links between the above variables and the cleft lip and palate. Therefore. Knowing the Relationship Between Cleft Lip and Palate Events with osteogenesis imperfecta with heterozygous mutation COL1A2 and triple helix DNA formation accompanied by Tetralogy of Fallot in children with a maternal history of catatonic schizophrenia followed by the use of valproic acid and type II diabetes mellitus. This research is a Systematic Review using the Preferred Reporting Items for Systematic Reviews and Meta-analyses method or commonly called PRISMA, this method is carried out systematically by following the correct research stages or protocols. The source was taken from the Google Scholar site with journals published in 2017-2023 and then screened the results of 1,870 journals. Journal clustering was carried out and the number of Q1 indexed journals was obtained in 4 journals, Q3 in 1 journal, and Q4 in 1 journal so that there were 6 journals extracted. The entire journal does not directly discuss the relationship between the research variables, but only provides an overview of the increased risk of celestial cleft conditions in babies if the expectant mother has type 2 diabetes mellitus conditions, osteogenesis imperfect, and the relationship of the two health conditions to the possibility of birth of the baby with the Tetralogy of Fallot condition, as well as the relationship of the baby to the condition of the cleft lip and palate and tetralogy of fallot